The bandwagons I followed as seed spices breeder: Bandwagons in seed spices - Divakara Sastry, E. V. (Journal of Spices and Aromatic Crops, 2025)
Bandwagons are waves that the breeders sail. This writing is based on the articles of Simmonds (1991) and Bernardo (2016) which point to different waves created by contemporary researches which influence breeders in their work. Seed spices are important group of crops of North and Northwestern India and this article chronicles the important phases through which seed spices breeding has undergone. While conventional methods of plant breeding have yielded results in seed spices, hybrid development is still taking off the ground, mutagenesis has proved its mettle and molecular breeding techniques are yet to make inroads in seed spices breeding. The author is of the view that not necessarily every bandwagon be adopted by seed spices breeders, but due diligence should be given if a new technique holds promise in helping a breeder. The author has chronicled his four decades of experience to guide new breed of breeders adopting spices breeding.